Edukasi Pemanfaatan Media “Merekah” Terhadap Upaya Optimalisasi Pendewasaan Usia Perkawinan (PUP) Di Desa Kelampaian Tengah Kecamatan Astambul Kabupaten Banjar Tahun 2024 - rafidah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2026)
Background: Early marriage has detrimental effects, including poverty, limited access to education, and domestic violence, which can result in physical and mental trauma and perpetuate intergenerational poverty. Addressing early marriage is crucial as it leads to poverty, isolation, and reduced opportunities for children. A strong commitment to reducing early marriage rates is essential to ensure children grow optimally, receive proper education, and achieve their dreams. To reduce early marriage rates, particularly in Astambul Subdistrict, South Kalimantan, the Midwifery Department of Poltekkes Kemenkes Banjarmasin, a health educational institution, supports government programs through community service activities. Objective: In 2024, enhance adolescents' knowledge and understanding of healthy reproduction through the Maturation of Marriage Age program and establish a youth forum focused on the importance of marriage age maturity in Kelampaian Tengah Village, Astambul Subdistrict, Banjar Regency. Methods: This community service activity was implemented through a health promotion program involving health education about the Maturation of Marriage Age. The steps included preparation, implementation, monitoring, and evaluation. The participants comprised 33 adolescents, 4 health cadres, and 1 midwife from the village. Results: Activity evaluation revealed a significant improvement in adolescents' knowledge regarding the importance of marriage-age maturity. Before the intervention, 17 participants (51.5%) had limited knowledge, with none possessing good knowledge. After the intervention, 20 participants (60.6%) demonstrated good knowledge, and a youth forum for marriage-age maturity awareness was established. Conclusion: This increase in knowledge is expected to contribute to marriage-age maturity, with the youth forum serving as a platform for discussion and awareness among adolescents.